Surgical affections of new born calves in selected upazilas of Bagerhat district, Bangladesh - Das, Sourav; Akter, Mst Antora; Alam, Md Rafiqul; Runa, Rukhsana Amin (Research in Agriculture Livestock and Fisheries, 2022)
The goal of this study was to determine the frequency of surgical affections and their associated risk factors in new born calves from the Mollahat, Fakhirhat, and Bagerhat Sadar upazilas of Bagerhat district. From 2015 to 2019, 5238 retrospective data were collected in all three upazilas. The surgical affections were categorized on the basis of sex and breed. The highest number of surgical affections found in all three upazila was navel ill with myiasis (60.44% in Mollahat upazila, 71.43% in Fakhirhat upazila and 60.11% in Bagerhat Sadar upazila). Surgical affections in calves vary in frequency according to the animal's sex and breed. Among the affections, navel ill with myiasis was higher (66.67% and 71.43%) in male than female calves (33.33% and 28.57%) in Mollahat and Fakhirhat upazila, respectively. However, in Bagerhat Sadar upazila congenital cataract was higher (71.43%) in male calves compared to female (28.57%). According to the breed, navel ill with myiasis were higher (64.85%) followed by umbilical hernia (18.74%) in cross breed calves. While navel ill with myiasis were higher (56.01%) followed by abscess (15.93%) in indigenous breed calves. According to the study, environmental conditions or management techniques can trigger surgical affections. It will be feasible to identify the prevalence of various surgical illnesses in this sector based on sex and breed based on the outcomes of this study in order to combat these diseases. Res. Agric., Livest. Fish.9(1): 43-48, April 2022